Hegel’s masters slave dialectics & slave rebellion of Spartacus - Shaloom Naeem (Research Parks Publishing LLC, 2020)
This paper investigates major points of the Hegel’s Masters slave Dialectics & Slave Rebellion of Spartacus. On this case, research has been pointed on the different research points of the Masters slave dialectics & slave rebellion of Spartacus.